HYDROïD Humanoid Robot Head with Perception and Emotion Capabilities: Modeling, Design, and Experimental Results - Alfayad, Samer; El Asswad, Mohamad; Abdellatif, A.; Ouezdou, Fethi B.; Blanchard, Arnaud; Beaussé, Nils; Gaussier, Philippe (Frontiers in Robotics and AI, 2016)
In the framework of the HYDROïD humanoid robot project, this paper describes the modeling and design of an electrically actuated head mechanism. Perception and emotion capabilities are considered in the design process. Since HYDROïD humanoid robot is hydraulically actuated, the choice of electrical actuation for the head mechanism addressed in this paper is justified. Considering perception and emotion capabilities leads to a total number of 15 degrees of freedom for the head mechanism which are split on four main sub-mechanisms: the neck, the mouth, the eyes and the eyebrows. Biological data and kinematics performances of human head are taken as inputs of the design process. A new solution of uncoupled eyes is developed to possibly address the master-slave process that links the human eyes as well as vergence capabilities. Modeling each sub-system is carried out in order to get equations of motion, their frequency responses and their transfer functions. The neck pitch rotation is given as a study example. Then, the head mechanism performances are presented through a comparison between model and experimental results validating the hardware capabilities. Finally, the head mechanism is integrated on the HYDROïD upper-body. An object tracking experiment coupled with emotional expressions is carried out to validate the synchronization of the eye rotations with the body motions.